Geoglomeris subterranea (Diplopoda, Glomerida, Glomeridae), the first morphologically non‐specialized semiaquatic glomerid millipede?. Issue 2 (3rd June 2022) - Valkay Haľková, Beáta; Tajovský, Karel; Grego, Jozef; Žurovcová, Martina; Mock, Andrej
Abstract: Geoglomeris subterranea Verhoeff 1908 is a small (2–3 mm), blind, and depigmented representative of the order Glomerida, with a predominantly Western European distribution. Towards Central Europe (the Czech Republic, Austria), the species is found only sporadically, and its occurrence is documented by a small number of individuals. Recently, we documented this species in three orographic units of Slovakia (Slovenské stredohorie mountain range, Slovak Karst, and Pieniny Mountains), always on limestone bedrock. These findings represent the easternmost documented occurrence of the species. Analysis of the mitochondrial COI gene confirmed the identity as the species G. subterranea from Western Europe. The circumstances of the findings in Slovakia were very surprising: At the first two localities, living individuals were repeatedly collected from the bottom of karst springs, together with stygobiont fauna. This expands our knowledge of semiaquatic millipedes and proves to be unique to the order Glomerida. In a subsequent study, we found a close association of this species with the rhizosphere within soil saturated by water at karst springs, in humid to wet habitats. Nonetheless, using detailed morphological study, no morphological adaptations to the aquatic environment were found.